Nilai Sufistik Pada Inskripsi Pintu Makam Sunan Kudus - nfn. Masyhudi (Berkala Arkeologi, 1995)
This paper described the cultural product of the people of the past in terms of the culture of art in writing. In addition, the teachings contained in the kind of literature have sufistic values that have a great influence on the development of Islam, especially in Java. This article is intended to reveal the value contained in the inscription on the door of the tomb of Sunan Kudus, which does not yet know the meaning of the content of the value implied in it.